2015
DOI: 10.1155/2015/842923
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Relapse Prediction Using Multiparametric MR Data Recorded during Follow-Up of GBM Patients

Abstract: Purpose. We have focused on finding a classifier that best discriminates between tumour progression and regression based on multiparametric MR data retrieved from follow-up GBM patients. Materials and Methods. Multiparametric MR data consisting of conventional and advanced MRI (perfusion, diffusion, and spectroscopy) were acquired from 29 GBM patients treated with adjuvant therapy after surgery over a period of several months. A 27-feature vector was built for each time point, although not all features could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The focus of this paper is the same as the focus of our previous paper (Ion-Margineanu et al, 2015): finding a map between multi-parametric MRI data acquired during the follow-up of GBM patients and the relapse of brain tumor after surgery, as described by the clinically accepted Response Assessment in Neuro-Oncology (RANO) criteria (Wen et al, 2010). We were motivated to conduct this study because of our excellent previous results where we could differentiate, based only on PWI features, between progressive and responsive follow-up GBM patients with 100% accuracy one month before the patients were labelled according to the RANO criteria.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of this paper is the same as the focus of our previous paper (Ion-Margineanu et al, 2015): finding a map between multi-parametric MRI data acquired during the follow-up of GBM patients and the relapse of brain tumor after surgery, as described by the clinically accepted Response Assessment in Neuro-Oncology (RANO) criteria (Wen et al, 2010). We were motivated to conduct this study because of our excellent previous results where we could differentiate, based only on PWI features, between progressive and responsive follow-up GBM patients with 100% accuracy one month before the patients were labelled according to the RANO criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Strong correlations have been reported between rCBV and cell density, and between rCBV and microvessel density in HGGs (Sadeghi et al, 2008). PWI has been reported to detect tumor recurrence at an earlier stage than cMRI (Ion-Margineanu et al, 2015) and has been shown to be useful in differentiating active glioma from radiation necrosis (Hu et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Modern multiparametric MRI techniques such as diffusion-weighted imaging (DWI) with apparent diffusion coefficient (ADC) mapping, dynamic susceptibility-weighted contrast-enhanced (DSC) perfusion imaging, and MR spectroscopy (MRS) allow a much deeper and still noninvasive insight into interpretation of brain lesions, resulting in greater specificity of diagnostic imaging, especially when in combination with amino acid PET imaging [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%